Kettévált ország - Papp, Gábor Zsigmond; Bartos, Bence; Dala, István; Kardos, Sándor; Lovasi, Zoltán; Tallér, Zsófia; Takáts, Eszter (Hungary : Bologna Film, 2017)
Twenty artists, writers, and directors with radically different political views reflect on the regime change in Hungary and the thirty years that followed. With appearances by: Róbert Alföldi, György Dörner, Károly Eperjes, György Fekete, Ádám Fischer, Marcell Jankovics, Imre Kerényi, Zsuzsa Koncz, György Konrád, Gábor Máté, Ádám Medveczky, Katalin Mezey, Lajos Parti Nagy, Gergely Péterfy, Géza Röhrig, Sándor Sára, György Spiró, Levente Szörényi, Géza Szőcs, and Béla Tarr.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films